Potentiality Analysis of Physical Development of International Airports Surrounding Zones (Journal of Engineering, 2020)
The areas surrounding Iraqi international airports generally suffer from a lack of interest in their planning in a manner compatible with the airport with the absence of integrated planning between the airport and the city. From here, the search problem appears. It is represented by a lack of interest in the integration of urban planning and airport planning and the lack of a clear policy to deal with the areas surrounding international airports. A desire to achieve the research aims to introduce compatible uses in the vicinity of airports and review the planning and global directions for dealing with the areas surrounding the airports within urban areas. In contrast, the second aspect of the research aims to assess the uses of the land surrounding the airports and determine their compatibility with the planning directions of these areas. The research studied the areas surrounding Baghdad International Airport and conducted a comprehensive survey of land uses within a distance of (4) km from the airport runway center. Then it conducted an analysis using geographical information systems(GIS) and studied the survey results, and assumed that the current uses of the areas surrounding international airports do not reflect the optimal use of these areas and, therefore, not exploiting the current capabilities and development opportunities provided by the airport for the surrounding areas. The research hypothesis is tested through the use of (GIS )and displaying the results of the field survey of land uses within the study area.Furthermore, the methodology of comparative spatial analysis was done by monitoring the current situation through (GIS) and analyzing the result and comparing it with international standards to achieve results that contribute to attaining physical development. The first part of the research presents an introduction to international airports that are one of the most significant urban nodes in the city. The surrounding areas have many features that require regulation and coordination. The presence of incompatible uses in the vicinity of the airport leads to the loss of the advantages provided by the airport and the occurrence of adverse effects on the surrounding areas. Part two introduced compatible uses in the vicinity of airports. Part Three analyzed the case study of the areas surrounding Baghdad Airport. Then the results of the field survey showed that there are incompatible uses and the absence of compatible uses, and this case requires the identification of many planning procedures and benefiting from global trends in planning these areas.